1998
DOI: 10.1016/s0014-5793(98)01073-4
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids as natural uncouplers preventing generation of O⋅−2 and H2O2 by mitochondria in the resting state

Abstract: Both natural (laurate) and artificial (m-chlorocarbonylcyanide phenylhydrazone; CCCP) uncouplers strongly inhibit O c3 2 and H 2 O 2 formation by rat heart mitochondria oxidizing succinate. Carboxyatractylate, an ATP/ADP antiporter inhibitor, abolishes the laurate inhibition, the CCCP inhibition being unaffected. Atractylate partially releases the inhibition by laurate and decelerates the releasing effect of carboxyatractylate. GDP is much less effective than carboxyatractylate in releasing the laurate inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
107
0
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(120 citation statements)
references
References 25 publications
12
107
0
1
Order By: Relevance
“…In the PMA-stimulated NADPH system, it could cause dissociation of inhibitors of components of the NADPH complex, promote an ideal membrane environment for enzyme function, promote the phosphorylation or translocation of p47 phox (15,23,25), stimulate the NADPH oxidase proton pump (10,26), activate or promote PKC translocation (12,23,(27)(28)(29), stimulate the cell, mimicking, when in the micellar state, particulate stimuli (14,22), or stimulating the cell via the generation of eicosanoids (6). Regarding the mitochondrial-derived superoxide production, AA could act by its known mitochondrial uncoupling ability (carrying protons across the inner mitochondrial membrane), stimulating the opening of the permeability transition pore or acting as a prooxidant, and affecting electron transport (10,30,31). AA is a substrate for many components of the cytochrome P-450 complex, known to produce superoxide (7).…”
Section: Discussionmentioning
confidence: 99%
“…In the PMA-stimulated NADPH system, it could cause dissociation of inhibitors of components of the NADPH complex, promote an ideal membrane environment for enzyme function, promote the phosphorylation or translocation of p47 phox (15,23,25), stimulate the NADPH oxidase proton pump (10,26), activate or promote PKC translocation (12,23,(27)(28)(29), stimulate the cell, mimicking, when in the micellar state, particulate stimuli (14,22), or stimulating the cell via the generation of eicosanoids (6). Regarding the mitochondrial-derived superoxide production, AA could act by its known mitochondrial uncoupling ability (carrying protons across the inner mitochondrial membrane), stimulating the opening of the permeability transition pore or acting as a prooxidant, and affecting electron transport (10,30,31). AA is a substrate for many components of the cytochrome P-450 complex, known to produce superoxide (7).…”
Section: Discussionmentioning
confidence: 99%
“…The heart has an abundant level of these proteins, particularly UCP2 (5). It has been postulated that the mild uncoupling ability of fatty acids is sufficient to maintain the mitochondrial membrane potential below a threshold level and prevent ROS formation by the respiratory chain (11). Differences in the uncoupling ability of oleate and palmitate have also been reported in model mitochondrial vesicles (22).…”
Section: Discussionmentioning
confidence: 99%
“…(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) at Complex I (by a yet unresolved mechanism, O 2 . is released to the matrix) (2) and via autooxidation of the ubisemiquinone anion radical at Complex III (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11), where O 2 . could be released into both sides of the membrane (2).…”
mentioning
confidence: 99%
“…FAOOH may also decompose to toxic epoxy acids and ␣,␤,␥,␦-unsaturated aldehydes (18). It has been found that even a slight increase of H ϩ backflux into the matrix may substantially suppress mitochondrial ROS formation (7)(8)(9)(10)(11) synthesis also suppresses ROS formation (7)(8)(9); therefore most ROS are produced in the non-phosphorylating state. This effect of uncoupling or ATP synthesis is due to increased respiration and hence concomitantly shortened lifetime of UQ .…”
mentioning
confidence: 99%